PENGARUH PERSONALITY DAN SHOP ENJOYMENT TERHADAP IMPULSE BUYING BEHAVIOR YANG DIMEDIASI IMPULSE BUYING TENDENCY - Kharisma, AA Istri Sandya; Ardani, I Gusti Agung Ketut Sri (E-Jurnal Manajemen, 2018)
Increased economic growth and consumer demand led to the community especially in Denpasar began to shift from traditional markets to modern retail stores that offer the concept of one stop shopping. This research was conducted on Hypermart Mallbali Galeria consumers who live in Denpasar City. Size of sample taken as many as 114 people with purposive sampling method. The analysis technique used is path analysis and test of sobel. The results showed that each variable personality and shop enjoyment have positive and significant effect on impulse buying tendency. This study also suggests impulse buying tendency significantly positively affects impulse buying behavior, besides impulse buying tendency also significantly mediate the relationship of personality to impulse buying behavior and shop enjoyment to impulse buying behavior. The study found that each variable personality and shop enjoyment have positive and significant effect on impulse buying behavior. This research is expected to be used as a study material and add additional references related to the variables studied and become a consideration for Hypermart Mall Bali Galeria in meeting the needs and desires of consumers.